Structure, biochemistry, and biology of PAK kinases - Kumar, Rakesh; Sanawar, Rahul; Li, Xiaodong; Li, Feng (Gene, 2017)
PAKs, p21-activated kinases, play central roles and act as converging junctions for discrete signals elicited on the cell surface and for a number of intracellular signaling cascades. PAKs phosphorylate a vast number of substrates and act by remodeling cytoskeleton, employing scaffolding, and relocating to distinct subcellular compartments. PAKs affect wide range of processes that are crucial to the cell from regulation of cell motility, survival, redox, metabolism, cell cycle, proliferation, transformation, stress, inflammation, to gene expression. Understandably, their dysregulation disrupts cellular homeostasis and severely impacts key cell functions, and many of those are implicated in a number of human diseases including cancers, neurological disorders, and cardiac disorders. Here we provide an overview of the members of the PAK family and their current status. We give special emphasis to PAK1 and PAK4, the prototypes of groups I and II, for their profound roles in cancer, the nervous system, and the heart. We also highlight other family members. We provide our perspective on the current advancements, their growing importance as strategic therapeutic targets, and our vision on the future of PAKs. •PAKs act as modifiers of the cell surface and intracellular signaling cascades.•PAKs function both in the cytoplasm and nucleus and regulation of gene expression.•Relevance of PAKs ranges from cellular homeostasis to pathobiology of human disease.•PAKs are dysregulated in cancer, and neurological, cardiac and other disorders.•Modifying PAK activity has emerged as a therapeutic approach for many disorders.